Evaluation of Infrastructure Resilience and Analysis of Obstacle Factors in Northeast Sichuan Economic Zone - Wang, Yikai (Journal of Research in Science and Engineering, 2025)
Based on the PSR framework, an infrastructure resilience evaluation model was developed to study the development of infrastructure resilience in the Northeast Sichuan Economic Zone from 2014 to 2023. Using factor analysis and entropy value methods, along with game theory, the weights of each evaluation indicator were determined. The results were visualized using ArcGIS, and the obstacle degree model was used to identify key constraining factors. The findings indicate that the overall infrastructure resilience in the northeast Sichuan economic zone is on the rise. The ‘Dual-core’ development pattern of Nanchong and Dazhou is evident, with significant differences in infrastructure resilience levels between cities. The main obstacles to enhancing infrastructure resilience in the study area include industrial structure, energy supply, terrain slope, and population distribution.